2009
DOI: 10.1111/j.1365-2249.2009.03890.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic defect of the immune system in children with Down syndrome: a review

Abstract: SummaryDown syndrome (DS) is the most frequent cause of mental retardation in man. Immunological changes in DS have been observed since the 1970s. The neurological system appears to be ageing precociously, with early occurrence of Alzheimer disease; until now, the observed immunological differences have been interpreted in the same context. Looking back at past and present results of immunological studies in DS children in relation to the clinical consequences they suffer, we conclude that it is more likely th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
214
0
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(237 citation statements)
references
References 69 publications
(88 reference statements)
10
214
0
13
Order By: Relevance
“…and suppressor T cells) and NK cells that are thought to be related to the increased susceptibility to infection, autoimmune disorders, and malignancies [10]. It may predispose DS patients to post-infectious glomerulonephritis.…”
Section: Discussion and Brief Reviewmentioning
confidence: 99%
“…and suppressor T cells) and NK cells that are thought to be related to the increased susceptibility to infection, autoimmune disorders, and malignancies [10]. It may predispose DS patients to post-infectious glomerulonephritis.…”
Section: Discussion and Brief Reviewmentioning
confidence: 99%
“…DS is associated with several complex clinical features including immunological abnormalities (4)(5)(6)(7)(8), and it has long been noticed that patients present abnormal thymuses, characterized by lymphocyte depletion, cortical atrophy, and loss of corticomedullary demarcation (9,10). In addition to higher susceptibility to infections-as evidenced during the H1N1 2009 pandemic where the likelihood of death was 300 times greater for DS patients (11)-DS is characterized by increased frequency of organ-specific autoimmune disorders and of lymphoid and myeloid leukemias, contrasting with a decreased risk for allergic diseases, particularly asthma (12,13).…”
mentioning
confidence: 99%
“…Alteration in the immune system, such as functional and morphological thymus abnormalities (Bloemers et al, 2011;Karl et al, 2012), lymphocytopenia, and alteration in differentiation, maturation, and activation of the T lymphocyte (Guazzarotti et al, 2009;Lorenzo et al, 2013) is frequently observed in DS individuals (Kusters et al, 2009). It can be responsible for increased incidence of infections, mainly in the respiratory tract (Bloemers et al, 2010;Broers et al, 2012), and occurrence of autoimmune disease in DS (Gillespie et al, 2006;Pellegrini et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…DS also present functional and morphological alterations of the thymus that is smaller (Kusters et al, 2009;Lorenzo et al, 2013), possibly as a result of the increase of cytokines as gamma-interferon (gamma-IFN), and tumor necrosis factor (alpha-TNF) (Murphy et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation